Homeward bound : the incredible journey [videorecording (DVD)] - Dunham, Duwayne; Hays, Robert, 1947-; Greist, Kim; Smart, Jean; Fox, Michael J., 1961-; Field, Sally; Ameche, Don; Burnford, Sheila, 1918-1984 (Walt Disney family film collection, 1999)
A fun-loving bulldog, a wise old golden retriever, and a hilarious Siamese cat travel through the rugged Sierras in a search of their missing human family.